2007
DOI: 10.1007/s12031-007-9015-9
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Disruption of the Galanin Gene Attenuates Inflammatory Responses in Murine Skin

Abstract: The release of neuropeptides from primary sensory nerve fibers has been implicated in the modulation of local immune responses in surface tissues, such as the skin and the gastrointestinal mucosa, thereby inducing neurogenic inflammation, which is characterized by plasma extravasation and vasodilatation. In addition, cytokines, either alone or in conjunction with neuropeptides, initiate recruitment of immunocompetent cells such as neutrophils during the initial phases of inflammation. Growing evidence suggests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…After galanin administration, MPO activity and the acinar cell necrosis score returned to normal levels in the galanin-KO mice, (Bhandari et al, 2010b). However, the reduction in neutrophil accumulation, reflected by reduced MPO activity, in galanin-KO mice is not exclusively restricted to AP and seems to be a more general phenomenon of inflammation, because it has also been observed with inflammatory skin responses (Schmidhuber et al, 2008).…”
Section: B Acute Pancreatitismentioning
confidence: 86%
See 1 more Smart Citation
“…After galanin administration, MPO activity and the acinar cell necrosis score returned to normal levels in the galanin-KO mice, (Bhandari et al, 2010b). However, the reduction in neutrophil accumulation, reflected by reduced MPO activity, in galanin-KO mice is not exclusively restricted to AP and seems to be a more general phenomenon of inflammation, because it has also been observed with inflammatory skin responses (Schmidhuber et al, 2008).…”
Section: B Acute Pancreatitismentioning
confidence: 86%
“…Galanin-OE mice displayed a significant reduction in cutaneous plasma extravasation induced by mustard oil (Holmberg et al, 2005a). In addition, galanin-KO mice exhibited a deficit in neutrophil accumulation in skin after exposure to noxious heat, carrageenan, or TNF-a (Schmidhuber et al, 2008).…”
Section: B Skinmentioning
confidence: 98%
“…Recently, Schmidhuber et al. 32 described an important role for galanin in neurogenic inflammation in the murine skin. Our data suggest a similar phenomenon may occur in the pancreas, indicative of a possible role for galanin in neurogenic inflammation, however, further studies are required to establish this 8,33 …”
Section: Discussionmentioning
confidence: 99%
“…We also demonstrated that the related peptides galanin-like peptide (GALP) and alarin inhibited inflammatory edema formation mediated by substance P and calcitonin gene-related peptide (CGRP) in murine dorsal skin Santic et al 2007). Furthermore, we have examined cutaneous inflammatory responses in galanin knockout mice; however, it was not possible to fully elucidate the role of galanin in the cutaneous microvasculature, as these mice exhibit a developmental deficit that could be responsible for the lack of neurogenic inflammation observed (Schmidhuber et al 2008). …”
Section: Introductionmentioning
confidence: 99%